Note on the convergence analysis of homotopy perturbation method for fractional partial differential equations - Elbeleze, Asma Ali; Kilicman, Adem; M. Taib, Bachok (Hindawi Publishing Corporation, 2014)
We apply the homotopy perturbation method to obtain the solution of partial differential equations of fractional order. This method is powerful tool to find exact and approximate solution of many linear and nonlinear partial differential equations of fractional order. Convergence of the method is proved and the convergence analysis is reliable enough to estimate the maximum absolute truncated error of the series solution. The fractional derivatives are described in the Caputo sense. Some examples are presented to verify convergence hypothesis and simplicity of the method.